2002
DOI: 10.1152/ajpcell.00443.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of aspartate residues in Ca2+ affinity and permeation of the distal ECaC1

Abstract: The Ca(2+) affinity and permeation of the epithelial Ca(2+) channel (ECaC1) were investigated after expression in Xenopus oocytes. ECaC1 displayed anomalous mole-fraction effects. Extracellular Ca(2+) and Mg(2+) reversibly inhibited ECaC1 whole cell Li(+) currents: IC(50) = 2.2 +/- 0.4 microM (n = 9) and 235 +/- 35 microM (n = 10), respectively. These values compare well with the Ca(2+) affinity of the L-type voltage-gated Ca(2+) (Ca(V)1.2) channel measured under the same conditions, suggesting that high-affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 29 publications
3
26
1
Order By: Relevance
“…Site-directed Mutagenesis of the Rabbit ECaC-TRPV5-The cDNAs coding for the wild-type ECaC-TRPV5 (GenBank TM AJ133128) (17) and the wild-type CaT2-TRPV5 (GenBank TM AF209196) (18) were obtained after reverse transcription of rabbit distal tubule mRNA as reported before (7). ECaC-TRPV5 and CaT2-TRPV5 were subcloned into the pT7TS vector (generously provided by Dr. Paul A. Krieg, University of Texas) using exonuclease III (19) for optimal expression in Xenopus laevis oocytes.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Site-directed Mutagenesis of the Rabbit ECaC-TRPV5-The cDNAs coding for the wild-type ECaC-TRPV5 (GenBank TM AJ133128) (17) and the wild-type CaT2-TRPV5 (GenBank TM AF209196) (18) were obtained after reverse transcription of rabbit distal tubule mRNA as reported before (7). ECaC-TRPV5 and CaT2-TRPV5 were subcloned into the pT7TS vector (generously provided by Dr. Paul A. Krieg, University of Texas) using exonuclease III (19) for optimal expression in Xenopus laevis oocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Run-off transcripts were prepared using methylated cap analog m 7 G(5Ј)ppp(5Ј)G and T7 RNA polymerase with the mMessage mMachine ® transcription kit (Ambion, Austin, TX). Expression of CaT2-TRPV5 Wild Type, ECaC-TRPV5 Wild Type, and Mutants in Xenopus Oocytes-Female Xenopus laevis clawed frog (Nasco, Fort Atkinson, WI) were anesthetized by immersion in 0.1% tricaine or MS-222 (3-aminobenzoic acid ethyl ester, Sigma) for 15 min before surgery as detailed before (7,20). cRNA was injected at a concentration of 0.46 -4.6 ng per oocyte depending upon the channel (wild type or mutant) being expressed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the nonpolar amino acids were replaced by a polar amino acid, Ser, and the polar amino acids were replaced by a small, nonpolar 1 The abbreviations used are: GFP, green fluorescence protein; GST, glutathione S-transferase. amino acid, Ala. Gly is classified as a polar amino acid and was thus replaced by Ala. Because it has been reported that the negatively charged amino acids Glu and Asp in the transmembrane domain contribute to ion selectivity in voltage-gated Ca 2ϩ channels (30,31) and ECaC (32,33) and to interaction with channel blockers (34,35), the remarkable Asp 341 was replaced by each of 7 amino acids, Glu, Lys, Arg, Thr, Asn, Ala, and Leu, and the positively charged amino acid His 353 was also replaced by each of 3 amino acids, Asp, Arg, and Ala. The mutant genes bearing these single amino acid substitutions were then introduced into cells of the mid1-⌬5 mutant, and the resulting transformants were examined for viability and Ca 2ϩ accumulation after exposure to ␣-factor.…”
Section: H3 Is Essential For Mid1mentioning
confidence: 99%